Impact of non-invasive ventilation on sympathetic nerve activity in chronic obstructive pulmonary disease - Haarmann, Helge; Nguyen, Xuan Phuc; Raupach, Tobias (Lung, 2017)
PurposeChronic obstructive pulmonary disease (COPD) is associated with elevated sympathetic nerve activity, which is probably linked to an increased cardiovascular risk, and may contribute to muscle dysfunction by heightened muscle vasoconstrictor drive. We hypothesized that resistive unloading of respiratory muscles by intermittent non-invasive ventilation (NIV) reduces sympathetic tone at rest and during subsequent handgrip exercise in patients with COPD.MethodsMuscle sympathetic nerve activity (MSNA) in the peroneal nerve, heart rate, blood pressure, CO2, and SpO2 were continuously recorded in 5 COPD patients with intermittent NIV and 11 control COPD patients without NIV. Static and dynamic handgrip exercises were performed before and after NIV.ResultsAt baseline, heart rate-adjusted MSNA (bursts/100 heart beats) did not differ between groups. NIV did not significantly affect MSNA levels at rest. However, during handgrip exercises directly following NIV, MSNA was lower than before, which was significant for dynamic handgrip (67.00 ± 3.70 vs. 62.13 ± 4.50 bursts/100 heart beats; p = 0.035 in paired t test). In contrast, MSNA (non-significantly) increased in the control group during repeated dynamic or static handgrip. During dynamic handgrip, tCO2 was lower after NIV than before (change by −5.04 ± 0.68 mmHg vs. −0.53 ± 0.64 in the control group; p = 0.021), while systolic and diastolic blood pressure did not change significantly.ConclusionsNIV reduces sympathetic activation during subsequent dynamic handgrip exercise and thereby may elicit positive effects on the cardiovascular system as well as on muscle function in patients with COPD.